Quantitative determination of BTEX in groundwater using dispersive liquid-liquid microextraction technique and GC-FID. - Gwanyuki, Doreen C. (My University, 2022)
“Dispersive liquid-liquid microextraction (DLLME) method was developed and validated for the extraction and analysis of aromatic hydrocarbons BTEX (benzene, toluene, ethylbenzene, xylene) in water samples. DLLME is a miniaturized version of liquid-liquid extraction (LLE) is a fast, efficient, and inexpensive microextraction method for pre-concentrating and extracting hydrocarbons.” “In this study the DLLME technique was used for the determination of BTEX in water samples. BTEX normally exists in trace amounts in environmental samples thus sample preparation plays a vital role. Sample preparation played a significant role in extracting the analytes, preconcentration of the sample and removal of interferences. This is important because GC-FID is a highly sensitive method and uses small volumes in the analysis. Sample preparation techniques such as liquid-liquid extraction are tedious, time-consuming, and insensitive, to counter these disadvantages and using large sample amounts of highly toxic hydrocarbons microextraction methods known as DLLME was used.” The importance of sample preparation is frequently ignored but it is a significant step in the analytical method because accuracy and precision depend largely on this step. Data obtained from this study compared with other microextraction methods from literature show that the extraction method demonstrated good precision, linearity, detection limit and enrichment factor for the extraction of the analysis. Extraction parameters such as the type of extracting solvent, extracting solvent volume, type of dispersion solvent, and the volume of the dispersion volume were optimized. Under optimum conditions, the detection limits for DLLME ranged from 1.8 to 2.6 μg. L−1 , repeatability from 2 to 4% and the extraction efficiency ranged from 60.1 to 95%. The applicability of the DLLME method was studied by gas chromatography with flame ionization detection system. The results demonstrated that the environmental water samples contained trace quantities of BTEX compounds, 2.7, 1.9, 0.3 and 0.4 μg. L−1 , respectively.”
Research Report submitted in partial fulfilment of the requirements for the degree of Master of Science by coursework and research report to the Faculty of Science, University of the Witwatersrand, Johannesburg